Modeling the Evolution of Construction Solutions in Residential Buildings’ Thermal Comfort - Reis, Inês F. G. (2021)
The evolution of the construction sector over the years has been marked by the replacement of high thermal inertia mass constructions by increasingly lighter solutions that are subject to greater thermal fluctuations and, consequently, thermal discomfort. To minimize these effects, energy demanding space conditioning technologies are implemented, contributing significantly to the sector’s share of global energy consumption. Enhanced constructive solutions involving phase-change materials have been developed to respond to the constructive thermal inertia loss, influencing buildings’ thermal and energy performance. This work aims to model the evolution of the construction over the last decades to understand to what extent constructive characteristics influence the occupants’ thermal comfort. For this purpose, typical and enhanced solutions representing distinct constructive periods were simulated using the EnergyPlus® software through its graphical interface DesignBuilder® and the thermal comfort of the different solutions was evaluated using the adaptive model for thermal comfort EN16798-1. The main results reveal that more restraining regulatory requirements are indeed mitigating thermal discomfort situations. However, overheating phenomena can rise, creating worrying consequences in the short-medium term. Thus, countries with mild climates such as Portugal, must pay special attention to these effects, which may be aggravated by climate change.